Pola Komunikasi Antar Budaya dalam Menjaga Keharmonisan Antar Etnis - Yusup, Muhammad; Marwani Syattar; Akhmad Saoqillah (Program Studi Komunikasi dan Penyiaran Islam, 2024)
Inter-ethnic harmony is an important factor in maintaining cultural diversity in Indonesia. The realization of harmonious communication patterns can be seen in good interaction and tolerance towards differences in different cultural backgrounds. This research aims to understand the patterns of intercultural communication that occur among Riau Malay and Sundanese ethnic Islamic boarding school students in the context of the Islamic boarding school environment. The methodology used is qualitative to gain an in-depth understanding of the interactions and communication dynamics between these two ethnic groups. involving 20 respondents, including Riau Malay and Sundanese ethnic students from several Islamic boarding schools. Data was taken using in-depth discussions, participant observation, and analysis of related documents. Then the results were processed using thematic analysis to identify existing intercultural communication patterns. The results of this research revealed the existence of supporting factors for intercultural communication in creating harmonious relations between Riau Malay and Sundanese ethnicities at the Tahfidzul-Quran Manba'ul Furqon Islamic Boarding School. The conclusion shows that the pattern of intercultural communication between Riau Malay and Sundanese ethnic Santri is based on tolerance, appreciation of differences, and mutual respect.